EVALUATION OF ECONOMIC EFFICIENCY OF MANUFACTURING FUEL BRIQUETTES OF HIGH QUALITY: Array - Polyansky, O.; Dyakonov, O.; Skrypnyk, O.; Dyakonov, V.; Buzina, I. (Municipal economy of cities. Series: «Economy science», 2020)
The paper evaluates the economic efficiency of the production of fuel briquettes of high quality. The main problems of the use of waste as fuel are noted. The main research results and a method for the efficient use of polyethylene waste as an energy-saturated component and a binder in the production of solid fuels are described. The technological scheme of a pilot plant and equipment necessary for the implementation of a method for producing briquettes are presented. As a result of improving the technology of manufacturing fuel briquettes, economic indicators were obtained for reducing the cost of electricity for grinding waste, increasing the cost of electric energy for mixing waste particles, reducing the cost of electricity, reducing the cost of electricity for drying, reducing the cost of electricity for sealed packaging.Technical and economic calculations show that the developed technology allows to reduce the time of technical cycles and reduce the technological area. A model of a technological process with an effective sequence of technological operations and the parameters of the optimal component composition are presented. The main factors that have a significant impact on the creation of the structural composition of solid multicomponent fuel are reflected. Defects of a new fuel briquette are shown. This perspective assessment, the relevance and practical importance of solving the problem of the efficient use of polyethylene waste in the production of solid multicomponent fuel is noted. A functional diagram of a device for technologically and economically optimal microwave drying of a briquette mixture in the manufacture of fuel briquettes is presented. This scheme allows you to fully automate the drying process of the briquette mixture, to obtain high quality briquettes and have total costs for the production of fuel briquettes and for drying the briquette mixture.